Lean Warehousing Model to improve the Order Fulfillment in a Metalworking Company - Anton, Alicia (2022)
n the present study, an evaluation of a company in the metalworking sector was carried out, which presents a delivery compliance indicator of 78.28% when in the sector this indicator varies between 85% and 90%, thus representing a relevant problem. Likewise, for the company this problem represents a loss of approximately 6.75% of its income. For this reason, the Lean Warehousing methodology will be implemented, which through its tools will allow improving inventory management in a way that reduces the percentage of non-compliance with the delivery of finished products and, therefore, reduces the negative economic impact. which causes this problem. Based on the literature review carried out, this methodology, through the Value Stream Mapping, 5S, Gemba and Work Standardization tools, together with the ABC Multicriteria analysis and the Managerial R,Q Model, allows the reduction of delivery times and increase in activities that add value. As a result of the implementation of the proposed model, a reduction of 21.1% of activities and 20.5% of the warehouse cycle time was obtained, the extended demand was also increased to 90%.